ANALISA DUKUNGAN KELUARGA DENGAN BEBAN ORANGTUA DALAM MERAWAT ANAK PENYANDANG CACAT TINGKAT SD DI SLB NEGERI SEMARANG - Dwi Retnaningsih; Indri Khizba Dini (Prosiding Seminar Nasional IPTEK Terapan (SENIT) 2016 Pengembangan Sumber Daya Lokal Berbasis IPTEK, 2016)
Having a mental disabled child is a tough challenge for many parents. This is a burden on families with children with special needs that gave rise to the various physical pressures, psychological, emotional, social and financial. Parents say having a mental disabled child is a test that causes severe irritation, angry, embarrassed, until the feeling of not accepting the fact. But, over time to accept the situation because the family have continued to support the development of children. The purpose of this study was to determine the relationship between family support with caregiver burden on parents for children with mental disability elementary level in the Outstanding Schools of Semarang. Research design using deskiptif correlation with cross sectional. Samples taken by proportional stratified random sampling of 124 parents of students. Research tool used questionnaires and bivariate analysis using Chi-squre test. The results of this study demonstrated an association between family support with caregiver burden on parents for children with mental disability elementary level in the Outstanding Schools of Semarang (pvalue=0,000). researchers further recommended to examine other factors that affect parents in caring for children with disabilities using different variables and methods. There are correlation between family support with caregiver burden on parents for children with mental disability elementary level in the Outstanding Schools of Semarang. Keywords : Family Support, Caregiver Burden Parents